1995
DOI: 10.1007/bf00262295
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of colony-stimulating factors in synovial fluid: potential clinical value

Abstract: In this study, 100 synovial fluid (SF) samples from patients with a variety of arthritides were assayed for levels of colony-stimulating factors (CSFs) using a human bone-marrow bioassay and enzyme immunoassays for granulocyte (G-) and granulocyte-macrophage (GM-) CSFs. GM-CSF was found more frequently in samples from rheumatoid arthritis (RA) subjects (49%) than in non-RA samples (29%). Absence of GM- but not G- or bioassay CSFs characterised samples from subjects with psoriatic arthritis and ankylosing spond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…In this study, we demonstrated that the GM-CSF is essential for CD1b+ iDC differentiation from FcγR-activated monocytes by showing that FcγR activated monocytes up-regulated GM-CSF and addition of anti-GM-CSF monoclonal Ab suppressed CD1b + DC differentiation. GM-CSF is thought to participate in autoimmune disease, with mRNA and protein detected in inflamed tissues of autoimmune disease patients (20). However, the relative potencies of FcγR activation vs. GM-CSF in inducing CD1b expression were different.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that the GM-CSF is essential for CD1b+ iDC differentiation from FcγR-activated monocytes by showing that FcγR activated monocytes up-regulated GM-CSF and addition of anti-GM-CSF monoclonal Ab suppressed CD1b + DC differentiation. GM-CSF is thought to participate in autoimmune disease, with mRNA and protein detected in inflamed tissues of autoimmune disease patients (20). However, the relative potencies of FcγR activation vs. GM-CSF in inducing CD1b expression were different.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with RA, GM-CSF is expressed in the synovial membrane and the level of GM-CSF is increased in the synovial fluid [39]. Increased expression of GM-CSF receptors is found on circulating monocytes [40], which promotes the subsequent maturation and activation of macrophages in the synovium.…”
Section: Extracellular Target In Ramentioning
confidence: 99%
“…85 Serum levels of GM-CSF are raised prior to the clinical onset of disease 86 and it is found at high levels in RA synovial fluid (up to 250 pg/mL). 87 Anti-GM-CSF antibodies have been shown to ameliorate CIA 88 and have separate and additive effect over IL-17 inhibition alone in suppressing Streptococcal cell wallinduced arthritis. 89 This has led to the development of biological agents to neutralize both soluble GM-CSF and block its receptor (GM-CSFR).…”
Section: Anti-gm-csf Therapiesmentioning
confidence: 99%